Scaffolds Functionalized with Matrix from Induced Pluripotent Stem Cell Fibroblasts for Diabetic Wound Healing. Issue 16 (29th June 2020) - Santarella, Francesco; Sridharan, Rukmani; Marinkovic, Milica; Do Amaral, Ronaldo Jose Farias Correa; Cavanagh, Brenton; Smith, Avi; Kashpur, Olga; Gerami‐Naini, Behzad; Garlick, Jonathan A.; O'Brien, Fergal J.; Kearney, Cathal J.
Abstract: Diabetic foot ulcers (DFUs) are chronic wounds, with 20% of cases resulting in amputation, despite intervention. A recently approved tissue engineering product—a cell‐free collagen‐glycosaminoglycan (GAG) scaffold—demonstrates 50% success, motivating its functionalization with extracellular matrix (ECM). Induced pluripotent stem cell (iPSC) technology reprograms somatic cells into an embryonic‐like state. Recent findings describe how iPSCs‐derived fibroblasts ("post‐iPSF") are proangiogenic, produce more ECM than their somatic precursors ("pre‐iPSF"), and their ECM has characteristics of foetal ECM (a wound regeneration advantage, as fetuses heal scar‐free). ECM production is 45% higher from post‐iPSF and has favorable components (e.g., Collagen I and III, and fibronectin). Herein, a freeze‐dried scaffold using ECM grown by post‐iPSF cells (Post‐iPSF Coll) is developed and tested vs precursors ECM‐activated scaffolds (Pre‐iPSF Coll). When seeded with healthy or DFU fibroblasts, both ECM‐derived scaffolds have more diverse ECM and more robust immune responses to cues. Post‐iPSF‐Coll had higher GAG, higher cell content, higher Vascular Endothelial Growth Factor (VEGF) in DFUs, and higher Interleukin‐1‐receptor antagonist (IL‐1ra) vs. pre‐iPSF Coll. This work constitutes the first step in exploiting ECM from iPSF for tissue engineering scaffolds. Abstract : Extracellular matrix (ECM)‐derived scaffolds are shown promise in a variety of tissue engineering applications. This work exploits, for the first time, ECM grown by cells differentiated from induced pluripotent stem cells for scaffold fabrication and examines their potential for diabetic wound healing. This ECM has previously been shown to be enriched in foetal‐like components, which can augment healing.